Human Resources Analytics: A Systematization of Research Topics and Research Agenda - Radha, P; L B, Muralidhar (International Research Journal of MMC, 2026)
The growing availability of workforce-related data and advances in analytical technologies have significantly transformed the field of Human Resource Management (HRM), giving rise to Human Resources Analytics (HR Analytics) as a strategic domain. HR Analytics refers to the systematic use of data, statistical analysis, and predictive models to improve human resource decision-making and organizational performance. Despite increasing academic and practitioner interest, the HR analytics literature remains fragmented, with diverse definitions, methodologies, and application areas. This study aims to systematize existing research on HR analytics by identifying key themes, methodological approaches, and emerging research gaps, while proposing a comprehensive future research agenda. Using a structured review of peer-reviewed journal articles indexed in Scopus, this study categorizes HR analytics research into core thematic areas, including talent acquisition, employee performance management, retention and turnover, learning and development, workforce planning, and employee well-being. The review highlights that early research predominantly focused on descriptive and diagnostic analytics, while recent studies increasingly emphasize predictive and prescriptive analytics to support strategic HR decisions. Advanced analytical techniques such as machine learning, artificial intelligence, and big data analytics are gaining prominence, enabling organizations to forecast employee behaviour and optimize human capital investments. Methodologically, the review reveals a dominance of quantitative approaches, particularly regression analysis, structural equation modelling, and data mining techniques, often using large organizational datasets. However, qualitative and mixed-methods studies remain limited, suggesting a need for deeper contextual understanding of how HR analytics is implemented and interpreted by decision-makers. Furthermore, most studies adopt a firm-level perspective, with limited attention to ethical concerns, data privacy, employee perceptions, and the potential unintended consequences of algorithm-driven HR decisions. The findings also indicate that while HR analytics is frequently linked to improved organizational performance and competitive advantage, empirical evidence remains inconsistent across industries and regions. This inconsistency underscores the importance of contextual factors such as organizational culture, analytical capability, leadership support, and HR professionals’ data literacy. The review identifies a significant gap between academic research and practical implementation, as many organizations struggle to translate analytical insights into actionable HR strategies. Based on the systematization of existing literature, this study proposes a future research agenda that emphasizes longitudinal research designs, cross-cultural studies, ethical and legal considerations, and the integration of employee-centric perspectives. Additionally, future studies should explore the role of HR analytics in promoting sustainable HRM, diversity and inclusion, and employee well-being. By providing a structured overview of the HR analytics research landscape, this study contributes to theory development and offers practical guidance for scholars and practitioners seeking to leverage analytics for strategic human resource management.